ПОТОКИ НАФТОВИХ ВУГЛЕВОДНІВ ЧЕРЕЗ МОРСЬКІ ОРГАНІЗМИ - Міронов, О. Г. (Marine Ecological Journal, 2023)
On the basis of long-term materials on interaction of marine organisms and oil hydrocarbons, the estimation of oil hydrocarbons flows through some organisms is carried out. In the Sevastopol Bay the bacterial association of seawater and bottom sediments transform 4.4 t and 0.2 t of oil hydrocarbons approximately. Mussels settling of the Sevastopol Bay berths accumulate 0.15 т oil hydrocarbons. Potentially (from calculation data) the zooplankton association of the Sevastopol Bay can accumulate and transfer 15 т oils per day. Possibility of the oil hydrocarbons flows through other organisms is discussed.